Teaching Learning Process Of English At RSBI Class (Rintisan Sekolah Bertaraf Internasional) At Smp Al Islam Surakarta In Academic Year 2011/2012 - Sulistyaningrum, Dyah (2012)
In this study, the writer describes the teaching learning process of English at the second year in SMP Al Islam Surakarta.The object of this research is teaching learning process of English at RSBI class in SMP Al Islam Surakarta in academic year 2011/2012. The objectives of the study are describing the material to teach English at SMP Al-Islam Surakarta, the syllabus that teaching English at SMP Al-Islam Surakarta, teaching method, the evaluation used to teach English, the strengths and weakness using many classroom activities to teach English. This research is a micro ethnography research. The methods of collecting data are observation, interview and documentation. The data achieved from information are related to the process of teaching learning process of English at RSBI class in SMP Al Islam Surakarta. The finding of this research shows that the teaching learning process in SMP Al Islam Surakarta at RSBI class is extended in bilingual sytem. In teaching learning process almost all of the subjects more presented in English and Indonesian language. SMP RSBI Al Islam Surakarta has a program in using English language. In the seventh grade, they have to use English 40% and 60% in Indonesian, and in eight grade they have to use English 50% and in Indonesian use 50%, too. Then in nine grade they use English 75% - 100%). The result of the study shows that the teaching learning process of English at the second year of RSBI class in SMP Al Islam Surakarta belongs to immersion model. The output of this school is mastering national standard education. The graduates are expected to have international standard consequently in all activities both of the teacher and students have to use English, as one of the international languages.